Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1128/cvi.00180-10
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Route of Administration and Dose Escalation for an Adenovirus-Based Influenza A Virus (H5N1) Vaccine in Chickens

Abstract: Highly pathogenic avian influenza (HPAI) virus causes one of the most economically devastating poultry diseases. An HPAI vaccine to prevent the disease in commercial and backyard birds must be effective, safe, and inexpensive. Recently, we demonstrated the efficacy of an adenovirus-based H5N1 HPAI vaccine (Ad5.HA) in chickens. To further evaluate the potential of the Ad5.HA vaccine and its cost-effectiveness, studies to determine the minimal effective dose and optimal route of administration in chickens were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…Adenovirus 5 (Ad5)-vectored candidate vaccines induce potent and protective immune responses against several pathogens in humans and a variety of animals [18,[23][24][25][26][27][28][29][30][31][32][33]. Although a trial of a candidate DNA/rAd5 HIV-1 preventive vaccine showed lack of efficacy [37] and the high prevalence of pre-existing anti-Ad5 immunity may have been a major limitation [38] in humans, replication-defective adenovirus vaccines are among the most attractive vectors for veterinary vaccine development, given the relative speed and low cost of development and production.…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus 5 (Ad5)-vectored candidate vaccines induce potent and protective immune responses against several pathogens in humans and a variety of animals [18,[23][24][25][26][27][28][29][30][31][32][33]. Although a trial of a candidate DNA/rAd5 HIV-1 preventive vaccine showed lack of efficacy [37] and the high prevalence of pre-existing anti-Ad5 immunity may have been a major limitation [38] in humans, replication-defective adenovirus vaccines are among the most attractive vectors for veterinary vaccine development, given the relative speed and low cost of development and production.…”
Section: Introductionmentioning
confidence: 99%
“…Immunization with Ad-based vaccines using different routes and dose regimens has been shown to have a significant effect on the type and strength of the induced immune responses (Holst et al 2010;Suda et al 2011;Steitz et al 2010). For example, parenteral administration is associated with diminished vaccine efficacy due to the presence of preexisting anti-Ad immunity.…”
Section: Prophylactic Vaccines Against Pandemic and Seasonal Influenzamentioning
confidence: 99%
“…Immunization with rAd vectored vaccines by different routes and doses can have a significant effect on the type and strength of the induced immune responses [98,99,100,101]. Similar to traditional vaccines, rAd vectored vaccines are usually delivered parenterally to stimulate humoral and cellular immune responses.…”
Section: Adenoviral Vectored Nasal Vaccines Can Bypass Pre-existinmentioning
confidence: 99%
“…Improved vaccines are required in order to induce rapid and sustained broad immunity, to allow mass vaccination campaigns and DIVA (differentiation between infected and vaccinated animals) strategies. The potency of a rAd vectored H5N1 vaccine expressing HA protein of A/Vietnam/1203/04 has been demonstrated [101,118] and can be significantly enhanced by fusion of HA protein with chicken CD154 in chickens [167]. Additionally, chickens can be effectively immunized by in ovo administration or aerosol spray of rAd vectored AI vaccines [125,168].…”
Section: Adenoviral Vectored H5n1 Vaccinesmentioning
confidence: 99%